Evaluation of geo-hazard risks in the pearl river delta based on geographic information system and weighted informativeness approach - Tang, Bo; Ren, Hao; Qiu, Jin-an; Miao, Cheng; Chen, Yinzhong (Frontiers in Environmental Science, 2024)
The implementation of the provincial geo-hazard risk survey in China holds significant guiding importance in assessing disaster risks on a large scale and across different regions. Taking the Pearl River Delta (PRD) in Guangdong Province as a case study, characterized by a highly developed economy and dense population yet facing challenges from geo-hazard, this study utilizes the risk assessment system for geo-hazard along with a substantial dataset on hidden dangers. The hazardousness levels, vulnerability, and overall risk are evaluated by applying the risk matrix method, Weighted Informativeness method, and grey correlation analysis method. The results indicate that: (1) The level of hazardousness posed by geo-hazards in the PRD is typically more pronounced in the central and eastern areas, while it is lower in the western regions. The severity of geo-hazards is primarily influenced by rainfall factors, while there is no direct correlation between slope factors and the occurrence of geo-hazards. The relationship between altitude and the likelihood of geo-hazards typically indicates that higher altitudes pose a greater risk. However, this pattern does not hold for the PRD; (2) The susceptibility to geo-hazard in the PRD is intricately linked to the level of regional economic advancement, with areas of medium to high vulnerability predominantly clustered around Guangzhou, Shenzhen, and Dongguan; (3) The likelihood of geohazard in the PRD, with a higher risk observed in the central part and lower risk in the surrounding areas, displaying a radial distribution pattern. Rainfall patterns and the level of economic development in the region significantly influence the assessment of geo-hazard risks in the PRD.